2018
DOI: 10.1101/507905
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetically regulated gene expression underlies lipid traits in Hispanic cohorts

Abstract: Plasma lipid levels are risk factors for cardiovascular disease, a leading cause of death worldwide. While many studies have been conducted in genetic variation underlying lipid levels, they mainly comprise individuals of European ancestry and thus their transferability to non-European populations is unclear. We performed genome-wide (GWAS) and imputed transcriptome-wide association studies of four lipid traits in the Hispanic Community Health Study/Study of Latinos cohort (HCHS/SoL, n = 11,103), replicated in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Interestingly, 11 out of these 13 genes had at least one VC-TWAS p-value <0.05 for one of the three pathologic AD showed that the genetic factor of gene ZNF234 on AD is potentially mediated through its gene expression, and the expression of this gene is also potentially involved in the mechanisms of both AD pathology indices of ߚ -amyloid and tangles. Besides AD, gene ZNF234 is also a known risk gene for lipid traits 42 . The genetically regulated gene expression of this gene might also affect lipid traits, thus leading to a pleiotropy phenomenon of AD and lipid traits 43 .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Interestingly, 11 out of these 13 genes had at least one VC-TWAS p-value <0.05 for one of the three pathologic AD showed that the genetic factor of gene ZNF234 on AD is potentially mediated through its gene expression, and the expression of this gene is also potentially involved in the mechanisms of both AD pathology indices of ߚ -amyloid and tangles. Besides AD, gene ZNF234 is also a known risk gene for lipid traits 42 . The genetically regulated gene expression of this gene might also affect lipid traits, thus leading to a pleiotropy phenomenon of AD and lipid traits 43 .…”
Section: Simulation Resultsmentioning
confidence: 99%
“…5455 For adequately powered colocalisation analyses, we considered a PP4 > 0.7 as being consistent with colocalisation between the two traits, similar to other recent studies. 56-59 We visualised colocalisation using the LocusCompareR R library. 60…”
Section: Statistical Analysesmentioning
confidence: 99%